\left \{ {{10-12x-30=6y-13} \atop {4y-63=20x-10y+2}} \right. <=>\\\ <=>\left \{ {{12x+6y=-7|*5} \atop {20x-14y=-65|*3}} \right.<=>\left \{ {{60x+30y=-35} \atop {60x-42y=-195}} \right. " alt="\left \{ {{10-6(2x+5)=6y-13} \atop {4y-63=5(4x-2y)+2}} \right. <=>\left \{ {{10-12x-30=6y-13} \atop {4y-63=20x-10y+2}} \right. <=>\\\ <=>\left \{ {{12x+6y=-7|*5} \atop {20x-14y=-65|*3}} \right.<=>\left \{ {{60x+30y=-35} \atop {60x-42y=-195}} \right. " align="absmiddle" class="latex-formula">
вычтем из первого уравнения второе
72y=160
![y=2\frac{2}{9} y=2\frac{2}{9}](https://tex.z-dn.net/?f=y%3D2%5Cfrac%7B2%7D%7B9%7D)
![12x+6*2\frac{2}{9}=-7\\\ 12x+6*\frac{20}{9}=-7\\\ 12x+2*\frac{20}{3}=-7\\\ 12x+\frac{40}{3}=-7\\\ 12x=-7-13\frac{1}{3}\\\ 12x=-20\frac{1}{3}\\\ x=-\frac{61}{3}:12\\\ x=-\frac{61}{36}\\\ x=-1\frac{25}{36} 12x+6*2\frac{2}{9}=-7\\\ 12x+6*\frac{20}{9}=-7\\\ 12x+2*\frac{20}{3}=-7\\\ 12x+\frac{40}{3}=-7\\\ 12x=-7-13\frac{1}{3}\\\ 12x=-20\frac{1}{3}\\\ x=-\frac{61}{3}:12\\\ x=-\frac{61}{36}\\\ x=-1\frac{25}{36}](https://tex.z-dn.net/?f=12x%2B6%2A2%5Cfrac%7B2%7D%7B9%7D%3D-7%5C%5C%5C+12x%2B6%2A%5Cfrac%7B20%7D%7B9%7D%3D-7%5C%5C%5C+12x%2B2%2A%5Cfrac%7B20%7D%7B3%7D%3D-7%5C%5C%5C+12x%2B%5Cfrac%7B40%7D%7B3%7D%3D-7%5C%5C%5C+12x%3D-7-13%5Cfrac%7B1%7D%7B3%7D%5C%5C%5C+12x%3D-20%5Cfrac%7B1%7D%7B3%7D%5C%5C%5C+x%3D-%5Cfrac%7B61%7D%7B3%7D%3A12%5C%5C%5C+x%3D-%5Cfrac%7B61%7D%7B36%7D%5C%5C%5C+x%3D-1%5Cfrac%7B25%7D%7B36%7D)